Dinâmica temporal da cobertura florestal na microrregião campanha central - RS - (:unkn) unknown (Universidade Federal do Pampa, 2011)
In recent years the Rio Grande do Sul has gone through a economic transition process, because, forestry emerges as a new alternative to this state. This paper aims to analyze the dynamics of forest cover in Microregion Campanha Central. Thematic maps of 2000 and 2010 were developed from Landsat 5 satellite images. The methodology consisted of the following steps: download and import images, digital image processing, pattern recognition and usage coverage and supervised digital classification. From the preparation of maps, one can observe that the forest cover had a total increase of 92,590.99 hectares in the micro. The counties that had been a most significant expansion Rosário do Sul and São Gabriel, a factor in the abandonment of farmland and forestry incentives. Moreover, one can see that there was an increase in forest area across the micro, Rosário do Sul had an increase of 37,685.87 hectares, 34,997.93 hectares of São Gabriel, Santa Margarida do Sul 11,945.62 hectares, and Santana do Livramento of 7961.57 hectares.
Keywords: Geoprocessamento; Imagens de satélite; Classificação digital; Geoprocessing; Satellite imagery; Digital rating; CNPQ::CIENCIAS AGRARIAS